2021
DOI: 10.3390/ijerph18041942
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Efficacy of the Face Shield and the Mask against Emitted and Potentially Received Particles

Abstract: There is currently not sufficient evidence to support the effectiveness of face shields for source control. In order to evaluate the comparative barrier performance effect of face masks and face shields, we used an aerosol generator and a particle counter to evaluate the performance of the various devices in comparable situations. We tested different configurations in an experimental setup with manikin heads wearing masks (surgical type I), face shields (22.5 cm high with overhang under the chin of 7 cm and ci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
2
23
0
5
Order By: Relevance
“…This suggests that wearing a face shield can provide some protection from cough droplets to those standing directly in front of the wearer. This was consistent with the findings from previous studies (Pan et al 2020 andWendling et al 2021).…”
Section: Discussionsupporting
confidence: 94%
“…This suggests that wearing a face shield can provide some protection from cough droplets to those standing directly in front of the wearer. This was consistent with the findings from previous studies (Pan et al 2020 andWendling et al 2021).…”
Section: Discussionsupporting
confidence: 94%
“…0.14 µm for SARS-CoV-2) [13,[25][26][27]. Face masks serve to reduce the number of particles, especially heavier ones [17,28,29]. Considering this, more attention should be paid to small particle sizes (diameter < 1 µm) when indoor viral aerosol dispersion is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory studies using mannikins have examined the potential effects of face shields but vary greatly in their design and their application to real-world settings. One study tested facing mannikins 25cm apart with the emitter sending an aerosol spray with particles with a range of size from less than 0.3µm to 10 µm; they found a reduction in particles received of 55% with face shields compared to 22% for a mask, and 97% for both 18 . A study with a mannikin 60cm from the spray found greater reductions and face shields providing greater protection than masks 19 .…”
Section: Discussionmentioning
confidence: 99%